Mental stress and hypertension - Kaczyńska, Anna; Gaciong, Zbigniew (Przewodnik Lekarza/Guide for GPs, 2008)
There is an association between hypertension, modern civilization and exposure to stress factors. Both recurrent acute and chronic stress may play a role in development of hypertension in susceptible individuals. In the human population one group displays especially hyper-reactive sympathetic response to stress. This group is predisposed to development of cardiovascular diseases such as hypertension. To prevent exaggerated blood pressure response to mental stress, pharmacological and non-pharmacological interventions are undertaken.